Ways to increase the EMF of semiconductor elements based on thermoelectric effects - Miagkyi, O.V.; Orel, R.P.; Meshkov, S.M.; Storozhenko, V.O. (Radiotekhnika, 2024)
The paper examines the development of the thermovoltaic effect in varizone semiconductor multilayer structures. The effect of the occurrence of electromotive force (EMF) in semiconductor samples without isotype transitions and metal-semiconductor barriers when heated along the sample under the thermovoltaic effect is studied. The possibility of obtaining stable thermally stimulated EMF in semiconductor samples with a heterogeneous composition, in particular in varizone semiconductors when they are heated, is considered. A semiconductor with a heterogeneous composition is simulated, in which the concentration of charge carriers, both electrons and holes, is enough to excite a significant electric current. Cases of both a single varizone semiconductor layer and a combination of several layers under different temperature conditions are considered. Both the definition of the EMF and numerous process characteristics are analyzed. It is confirmed that the appearance of a thermo EMF is caused by the non-equilibrium state and heterogeneity of the environment, as well as its bipolarity. It is shown that in a closed circuit with heterogeneous doping and variable width under uniform heating of the entire circuit, the EFM appears. The equation that determines the EFM ratio in various semiconductors is received. A thermophysical model based on the nonstationary heat equation with boundary conditions of the 2nd and 3rd kind for thermal field calculations is developed. A thermophysical model is created that characterizes a two-layer structure with smoothly changing parameters. The results of the numerical experiment made it possible to obtain the recommended temperature limits for the operation of the considered elements taking into account the SiGe solid solution and to calculate the value of the additional EMF.